Interval-Valued Intuitionistic Fuzzy INK-Ideals of INK-Algebra - K., Indhira.; M., Kaviyarasu.; V.M, Chandrasek (International Journal of Engineering and Technology, 2018)
Mathematical structures of Interim valued IF INK-ideal on INK-algebras are presented. We established that every IF- (INK)-ideal of an INK algebra A can be executed as an level ideal (INK) of an iv IF(INK) of U. As far as the idea of homomorphism, we talked about the cartesian result of i-v IF(INK)- ideal.Â Â Â